2021
DOI: 10.3389/fcvm.2021.748875
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Prognostic Value of Plasma Galectin 3 in HFrEF Related to the Etiology of Heart Failure

Abstract: Aim: The aim of present study is to evaluate the diagnostic and prognostic value of plasma galectin 3 (Gal-3) for HF originating from different causes.Methods: We investigated the plasma levels and expression of Gal-3 in cardiac tissues in two transgenic (TG) strains of mice with cardiomyocyte-restricted overexpression of either β2- adrenergic receptor (β2- AR TG) or Mammalian sterile 20-like kinase 1 (Mst1-TG) in the present study. Additionally, 166 patients suffering from heart failure with reduced ejection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that low hsa-miR-490 expression is associated with reduced HCC patient survival ( Wang et al, 2018 ; Yang et al, 2018 ). However, miR-490 expression has also been positively correlated with OS of patients with HCC, lung cancer, and multiple myeloma (MM) ( Zhang et al, 2013 ; Li et al, 2016 ; Lu et al, 2021 ). This may be due to the dual role of miR-490-5p in cancer regulation ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that low hsa-miR-490 expression is associated with reduced HCC patient survival ( Wang et al, 2018 ; Yang et al, 2018 ). However, miR-490 expression has also been positively correlated with OS of patients with HCC, lung cancer, and multiple myeloma (MM) ( Zhang et al, 2013 ; Li et al, 2016 ; Lu et al, 2021 ). This may be due to the dual role of miR-490-5p in cancer regulation ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%